The cost of conducting rapid assessment of avoidable blindness survey in Andhra Pradesh State, India - Pallerla, Srinivasa Reddy; Vaggu, Srikumar; Gudapati, Bala Krishna; Eda, Shiva Shankar (International Journal Of Community Medicine And Public Health, 2023)
Background: To determine the cost of conducting a rapid assessment of avoidable blindness survey in Andhra Pradesh State, India. RAAB is a simple rapid survey methodology that can provide data on prevalence and causes of blindness and visual impairment. As per the manual published by international centre for eye health, ICEH London United Kingdom the cost of doing a RAAB survey was US 20000 to 30000. No data were available regarding the cost required for doing the RAAB survey in India or from any other developing country. Hence the present study was conducted to arrive at the average cost of a RAAB survey in Indian scenario. Methods: The Andhra Pradesh right to sight society conducted RAAB surveys in three different tribal areas by three teams in the year 2009. The average cost of doing RAAB survey was arrived by calculating the mean expenditure of the three surveys. Results: The average cost of doing a RAAB survey in India was Rs.2, 30,541.66 (US 4,433.50). which was 15 to 22%of the cost mentioned in the RAAB Instruction Manual version 4.02 published by ICEH. Conclusions: As the cost of doing RAAB survey is very much less in India, this may encourage the epidemiologists and researchers to undertake the rapid assessment surveys with limited budget and can easily be repeated every 5 years to know the trends.